Short and Long-term Effects of Writing Intervention from a Psychological Perspective on Professional and Academic Writing in Higher Education – The EFL Writers’ Workshop - Keranen, Nancy; Merino Munive, Sara (Journal of Academic Writing, 2012)
Writing in higher educational settings is regarded as problematic for all but the most dedicated people (Silva, 2007). Many of the problems come from psychological states (internal-censors, fears, perfectionism, procrastination) deeply rooted in writing experiences (Boice, 1990). However, the literature addressing this is generally missing. A survey of writing-books, manuals, and research studies indicate that most approach writing from linguistic, stylistic, and rhetorical perspectives (Silva, 2007). This study attempted to fill this gap by examining a group of graduate students attending a writing workshop which specifically addressed psychological barriers to productive writing (Boice, 1990). The eight-week workshop consisted of classroom sessions in the first week and then moved to an online course management platform. The primary aim of the study was to note the changes in the students using data from their weekly writing reflections and discussion board comments in several forums and 8-month follow-up interviews. Findings indicate that the workshop had immediate effects on the writers but as the time passed the effects faded. The study looked to Threshold Concepts Theory (Meyer & Land, 2005) as a possible theoretical explanation for the loss of the temporary positive workshop results.